Fundamentals of signals and systems : using MATLAB - Kamen, Edward W. (Prentice-Hall, 1997)
Fundamental concepts - Systems defined by differential or difference equations - Convolution representation - The Fourier series and Fourier transform - Frequency-domain analysis of systems - Fourier analysis of discrete-time signals and systems - The Laplace transform and the transfer function representation - System analysis using the transfer function representation - Application to control - The z-transform and discrete-time systems - Design of digital filters and controllers - State representation - Appendices.